A Contemporary Reading of Vitruvius' Opening Statements and a Proposed New Partial Translation of De Architectura I.1. Issue 2 (4th May 2022) - Lefas, Pavlos
Abstract: The present paper offers a new reading of Vitruvius' opening statements in De Architectura I.1; it understands that the Roman author attempts to explain what architecture is by describing how architecture-related knowledge is acquired. It further understands that Vitruvius claims that the architect's scientia is born out of the bodily involvement with construction, as well as out of the exercise of the proper deductive reasoning. The knowledge required for the design and erection of sound buildings that can be integrated into the world order is akin to what we today name the "designerly" way of thinking and knowing, enriched with expertise on the realization of the design produced. Finally, it proposes a new translation of I.1 that produces a coherent text with no logical gaps.